Economic evaluation of five tobacco control policies across seven European countries - Leão, Teresa (2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Research on Nicotine and Tobacco. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.